Technical Study on Tin Mining Land Openings to Determine Post-Mining Reclamation Strategies - Deventi Nur Aeni; Harmin Sulistiyaning Titah (Politeknik Siber Cerdika Internasional, 2026)
Background: Post-mining land reclamation is a crucial component of sustainable mining practices aimed at restoring degraded land to its original condition or to a new, ecologically functional state. In the Kemingking area, extensive illegal alluvial tin mining has significantly reduced reclamation effectiveness and increased the risk of long-term environmental degradation. Inadequate spatial documentation of land disturbances has further complicated the formulation of effective reclamation strategies. Objective: This study aims to spatially analyze land openings resulting from both legal and illegal alluvial tin mining activities as a technical basis for formulating effective post-mining reclamation strategies. Method: The research employed a multitemporal remote sensing approach using satellite imagery from 2004 to 2022 combined with UAV-based photogrammetry conducted between 2022 and 2024. Geographic Information System (GIS) analysis was applied to identify land-clearing dynamics, delineate pit boundaries, and evaluate surface morphology changes over time. Result: The results demonstrate that medium-to-high-resolution UAV imagery (0.5–1 m) is more effective than satellite imagery in identifying land-clearing features, pit geometry, and surface morphology. Historical patterns of illegal land clearing from 2004 to 2019 were successfully mapped as baseline disturbance data. As of 31 December 2024, mapped land openings covered 44.79 ha of illegal mining areas and 110.32 ha of legal mining areas. Conclusion: Effective reclamation planning for alluvial tin mining areas requires integration of UAV-derived data and multitemporal GIS analysis. This approach provides essential technical inputs for landform reconstruction, pit reconfiguration, and material estimation for land regrading, thereby strengthening post-mining reclamation strategies.